DEVELOPMENT OF THE ASTA CITA PROGRAM THROUGH MSME INDUSTRY DOWNSTREAMING TO SUPPORT ECONOMIC GROWTH AND LABOR-INTENSIVE EMPLOYMENT - Dahlia, Dahlia; Sumardjono, Sumardjono; Lubis, Derman Janner (LPPM Univ. Ibn Khaldun Bogor, 2025)
Bogor, West Java, known as a region with high rainfall, has a number of distinctive culinary delights and diverse tourist destinations. In line with the development of MSMEs that continues to increase every year as a business entity that supports the National GDP by 60.5% and absorbs the workforce by 90.6%; an increasingly diverse range of processed food products are emerging. Food and beverage products as MSME products are currently increasing. Strengthening MSMEs through the downstreaming of the Bogor passion fruit syrup industry to improve community welfare is the theme of the community service grant program which is the 5th goal of Asta Cita. The community service process begins through team discussions with village governments, youth organizations, MSME groups and women's farmer groups. Digitalization, which is the main factor inhibiting MSME sales, in addition to Cost, Volume, Profit analysis in business management, is addressed through training in management and information technology. Supporting the development of digitalization, the results of this community service have produced outputs through the creation of a Google Sites site, a mock-up representing Bogor passion fruit syrup, and social media accounts. The PKM (Community Partnership Empowerment) grant has been provided as output in the form of passion fruit tree seeds, planting media, and fertilizer to reduce costs, increase syrup production volume and increase profits.